Research and evaluation in education and psychology integrating diversity with quantitative, qualitative, and mixed methods - Mertens, Donna M. (Thousand Oaks, California SAGE, 2024)
"Identify, evaluate, and practice good research using the sixth edition of Research and Evaluation in Education and Psychology: Integrating Diversity With Quantitative, Qualitative, and Mixed Methods by renowned scholar Donna Mertens. This introductory research methods text incorporates the viewpoints of various research paradigms into its descriptions of qualitative, quantitative, and mixed methods as well as program evaluation. The work covers five major paradigms: post-positivist, constructivist, transformative, pragmatic and Indigenous. Special emphasis on conducting research with culturally complex communities, based on the perspectives of feminists, ethnic/racial minorities, and people with disabilities is a hallmark of this text. In each chapter, the author carefully explains each step of the research process, from the literature review to analysis and reporting. Additionally, each chapter includes a published sample study and abstract to illustrate the concepts discussed in that chapter. This text works well as a core text for either a consumer-focused graduate-level course or a doctoral-level research methods course. The new edition gives extra attention to introductory terminology, research methods paradigms, and indigenous methods. Citations and references have all been updated to reflect the seventh edition of the Publication Manual of the American Psychological Association. Community engagement now features prominently throughout the book, including in literature reviews and examples throughout the text. Recent advances in mixed methods, new applications of theoretical frameworks, and the latest research examples will give students the most current instruction in research methods"-- Provided by publisher.
A brief history of research : paradigms, ethical practice, and contested territory -- Evaluation -- Focusing the research : literature review and community engagement -- Experimental and quasi-experimental research -- Causal comparative and correlational approaches -- Survey methods -- Single-case research -- Qualitative research and action research -- History, narrative inquiry, and autoethnography -- Mixed methods research -- Sampling -- Data collection -- Data analysis, interpretation, and use.
Includes bibliographical references (pages 471-489) and index.
Keywords: Education -- Research -- Methodology; Psychology -- Research -- Methodology